Dietary niacin and the risk of incident Alzheimer's disease and of cognitive decline. Issue 8 (16th July 2004) - Morris, M C; Evans, D A; Bienias, J L; Scherr, P A; Tangney, C C; Hebert, L E; Bennett, D A; Wilson, R S; Aggarwal, N
Abstract : Background: Dementia can be caused by severe niacin insufficiency, but it is unknown whether variation in intake of niacin in the usual diet is linked to neurodegenerative decline. We examined whether dietary intake of niacin was associated with incident Alzheimer's disease (AD) and cognitive decline in a large, prospective study. Methods: This study was conducted in 1993–2002 in a geographically defined Chicago community of 6158 residents aged 65 years and older. Nutrient intake was determined by food frequency questionnaire. Four cognitive tests were administered to all study participants at 3 year intervals in a 6 year follow up. A total of 3718 participants had dietary data and at least two cognitive assessments for analyses of cognitive change over a median 5.5 years. Clinical evaluations were performed on a stratified random sample of 815 participants initially unaffected by AD, and 131 participants were diagnosed with 4 year incident AD by standardised criteria. Results: Energy adjusted niacin intake had a protective effect on development of AD and cognitive decline. In a logistic regression model, relative risks (95% confidence intervals) for incident AD from lowest to highest quintiles of total niacin intake were: 1.0 (referent) 0.3 (0.1 to 0.6), 0.3 (0.1 to 0.7), 0.6 (0.3 to 1.3), and 0.3 (0.1 to 0.7) adjusted for age, sex, race, education, and ApoE e4 status. Niacin intake from foods was also inversely associated with AD (p for linear trend = 0.002 in the adjusted model). In an adjusted random effects model, higher food intake of niacin was associated with a slower annual rate of cognitive decline, by 0.019 standardised units (SU) per natural log increase in intake (mg) (p = 0.05). Stronger associations were observed in analyses that excluded participants with a history of cardiovascular disease (β = 0.028 SU/year; p = 0.008), those with low baseline cognitive scores (β = 0.023 SU/year; p = 0.02), or those with fewer than 12 years' education (β = 0.035 SU/year; p = 0.002) Conclusion: Dietary niacin may protect against AD and age related cognitive decline.